Impacts and effects of the use of medications by crew and passengers during air transport (Research, Society and Development, 2022)
During a flight, changes occur in the human body, whose possible reactions can influence the well-being and quality of health of medicine users, subject of scarce studies. The aim of this paper is to analyze the impacts and effects of medication use during air transport. Through a literature review and documentary research methodology, relevant facts about the precautions that should be taken regarding the use of medication in flights were considered. As a practical contribution, some important medications and their possible effects during flights are presented, as well as some warnings about medication interactions, and some advice for better quality air travel for the health of passengers and crew are given. As a theoretical contribution, this study gathers the scattered information presented in the literature about the problems that the use of medications during a flight can cause to the human body and possible recommendations. As social contribution, this study warns about the risks of self-medication, and establishes a basis for future discussions with society about the use of medication in flights.